PLACEMENT OF DOMESTIC GASTRONOMIC PRODUCTS IN TOURISM - CHALLENGES AND CHANCE - Dragin, Aleksandra; Blesic, Ivana; Pivac, Tatjana; Košić, Kristina; Demirović, Dunja (International Journal of Economic Practice and Policy, 2019)
Approximately 30% of tourist costs are allocated for the consumption of food and beverages, and often more in the case of local agricultural products. Therefore, the subject of research is to examine the links between domestic produced agricultural products and tourism on specific examples. In the first phase of the research focus is on examples of good and bad practice from different continents. The central task was to examine the situation of the mentioned topics in Serbia. For the case study is taken Srem District. Through the questionnaire, the views of local agricultural producers in Srem regarding the placement of their products were examined (who are their customers, whether the hotels/restaurants are interested in buying their products, whether they know how to sell their products to restaurants/hotels, there are some difficulties in such a sales chain (placement of goods), etc. In addition to the historical method, descriptive statistics (SPSS 17) have been used. The results of the survey provide an insight into the current situation and provide concrete guidelines for improving the cooperation of the tourism sector and the local community with positive multieffects to high number of stakeholders.